Registration of Import License for IVD’S In India. - Yashashri M, Inamdar (Asian Journal of Pharmaceutical Research and Development, 2023)
India is a huge market for medical devices and is constantly increasing last few years. The registration certificate and import license is mandatory for manufacturer of India who wishes to import any medical device in India. Indian Agent authorized by CDSCO is required for registering the medical device in India. Duly filled Form MD-14 is required to be submitted for import license registration and license obtained will be in Form MD-15. The review focuses on the regulations concerned to the registration procedures import for new medical device in India with latest amendments in the regulation concerned.